The global permutations of the Western publication regime - Erik Cohen (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group This article introduces the concept of the ‘publication regime’ into the current discourse on academia. This allows for a much deeper understanding of how publishing conglomerates and appointment and promotion procedures in Western universities are increasingly interlocked. It then turns to the global permutations of that regime as it is currently disseminated to other parts of the world. Using empirical examples drawn primarily from the field of tourism studies, we examine the problems engendered by the introduction of the regime’s appointment and promotion procedures of early career academic staff in universities in the emerging world regions. We specify the auxiliary mechanisms intended to ameliorate these problems, and draw attention to the neo-colonial implications of the disciplining process which these mechanisms are introducing into the academic life of the universities in the emerging regions. We argue that, as the Western publication regime is becoming increasingly globalized, local intellectual voices tend to be silenced by the regime’s growing hegemony, and call for the integration of non-Western perspectives into the framework of the publication regime.